2003
DOI: 10.1302/0301-620x.85b7.12633
|View full text |Cite
|
Sign up to set email alerts
|

The role of MRI and ultrasound imaging in Morton’s neuroma and the effect of size of lesion on symptoms

Abstract: We investigated 29 cases, diagnosed clinically as having Morton's neuroma, who had undergone MRI and ultrasound before a neurectomy. The accuracy with which pre-operative clinical assessment, ultrasound and MRI had correctly diagnosed the presence of a neuroma were compared with one another based on the histology and the clinical outcome. Clinical assessment was the most sensitive and specific modality. The accuracy of the ultrasound and MRI was similar and dependent on size. Ultrasound was especially inaccura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
84
2
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 23 publications
3
84
2
7
Order By: Relevance
“…Diagnosis is mainly based on clinical assessment, which is based on the patient's history and the clinical examination [9,17,18]. Ultrasound and MRI are not essential for the diagnosis of Morton's neuroma, because asymptomatic interdigital nerve enlargement is common [8,19,20]. Occurrence of a neuroma remains unreliable unless it is clinically symptomatic [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis is mainly based on clinical assessment, which is based on the patient's history and the clinical examination [9,17,18]. Ultrasound and MRI are not essential for the diagnosis of Morton's neuroma, because asymptomatic interdigital nerve enlargement is common [8,19,20]. Occurrence of a neuroma remains unreliable unless it is clinically symptomatic [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…28 Owens et al also found that a combination of positive clinical tests was a good indicator for the presence of PDN. 22 The two clinical tests used in this current study were also found to be the most sensitive tests in a recent comparison of clinical and radiological diagnosis.…”
Section: Discussionmentioning
confidence: 96%
“…9 This said, clinical tests may be just as useful especially in detecting smaller lesions which can be missed by ultrasound and MRI, yet which cause the sufferer just as much discomfort. 6,28 Indeed, Sharp et al found that clinical tests were more sensitive in the detection of PDN than either ultrasound or MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is usually confirmed by the use of Radiographs, Ultrasound or Magnetic Resonance Imaging (MRI). However, it has been reported that physical examination and the production of Mulder's sign is still the most sensitive and specific method of diagnosing Morton's Neuroma [17]- [20]. Morton's neuroma can be managed conservatively using arch supports, wearing wide toe box shoes, avoidance of high-heels, and padding or taping with the aim of dispersing weight bearing from the site of the neuroma to avoid compression and therefore symptoms.…”
Section: Introductionmentioning
confidence: 99%